The politics of protest in newspaper campaigns: dissent, populism and the rhetoric of authenticity - Birks, Jen (Palgrave Macmillan, 2011)
Newspaper campaigns embody newspaper’ most emphatic claims to speak for ‘the people’, and as such are generally regarded as populist. However, they can be oppositional, engaging in dissent of one sort or another, and often assume a certain amount of political engagement with that dissent on the part of the audience. This article examines the potential of newspaper camapigns to facilitate the political engagement of citizens through the politics of protest. It draws on qualitative analysis of seven campaigns that ran in the Scottish press between 2000 and 2005, and semi-structured interviews with relevant journalists. The distinction between legitimate protest and manipulative populism is made in terms of: (a) the rhetoric and strategies of political representation, participation and influence and (b) the construction of political legitimacy in terms of the public interest and the moral authority of the ‘victim’. It is argued that populist impulses dominate, driving a tendency to use discourses of emotional authenticity and offence to legitimise demands for a plebiscitary response to popular of ‘victim’ preference and to close down controversy and debate, with the principal objective marketing the newspaper as an influential community champion.